Pengaruh Teknologi Membangun Budaya Organisasi : Penggunaan Fingerprint dan Aplikasi Presensi di Pondok Pesantren Darul Arifin Jambi - Andi Zainal Abidin; Muhammad Taraki; Lidin Wiwah Jaya Putra; Jamrizal Jamrizal; Samsu Samsu (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Technology plays an important role in organizational culture if managed well and is very helpful in the rotation of an organization's journey. Finger print, for example, is a technological tool that contributes to building organizational culture. This tool not only functions as an attendance system, but also creates time discipline, transparency, and accountability among team members. Technology implementations like these demonstrate how technology can be used to support an organization's core values. Apart from that, applications such as E Pesantren Presence also provide digital solutions for monitoring attendance in real-time, which is very helpful for based organizations. Of course, the Head of Human Resources really feels helped by the contribution of technology in achieving organizational goals and it is very beneficial for teachers to have a disciplined character to apply and set an example for the students.